2017
DOI: 10.1016/j.ijid.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotypes 68 and 58 are the most prevalent genotypes in women from quilombo communities in the state of Maranhão, Brazil

Abstract: A distinct profile of high-risk HPV genotypes was detected, with predominance of types 68 and 58. It is possible that the results of the present study are due to specific characteristics of the population, which is geographically isolated and maintains conservative sexual habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
2
8
1
2
Order By: Relevance
“…In Northeastern Brazil, a number of papers have been published on HPV prevalence and type distribution among women with cytological and/or histological alterations [14,[30][31][32][33][34][35]. However, to the best of our knowledge, HPV prevalence among women with cervical lesions in the state of Sergipe, located in this region, has never been assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Northeastern Brazil, a number of papers have been published on HPV prevalence and type distribution among women with cytological and/or histological alterations [14,[30][31][32][33][34][35]. However, to the best of our knowledge, HPV prevalence among women with cervical lesions in the state of Sergipe, located in this region, has never been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Low-risk types 16 4.7 region of Brazil, HPV 68 was the most prevalent, but only women from quilombo communities with cytological abnormalities were assessed [35]. These results highlight the importance of assessing the prevalence of HPV types in other populations from this Brazillian region, which is associated with a high rate of cervical cancer incidence [2,38].…”
Section: Hpv Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with another study in the same region of Kenya where a high HPV68 prevalence among HIV-infected women was found 33 . A study conducted in an isolated rural community in Brazil reported HPV68 as the most prevalent genotype, however it was not present in women with cytological abnormalities 45 . The epidemiological importance of HPV68 needs to be further evaluated, especially as assay-related variation in HPV68 detection has been reported 46 .…”
Section: Hpv Genotypesmentioning
confidence: 95%
“…The second batch (N = 383) was tested at AML laboratory, Antwerp, Belgium, using the TaqMan-based qPCR assay (RIATOL, Sonic Healthcare Benelux, Antwerp, Belgium) which detects 17 HPV genotypes and β -globin in seven multiplex reactions. These HPV types include all 12 high-risk types (HPV16, 18,31,33,35,39,45,51,52,56,58,59), three probably high-risk types (HPV53, 66 and 68), one low-risk type (HPV6) and one undetermined risk type (HPV67) [32]. All HC2 positive and a subset of HC2 negatives samples were retested using the TaqMan-based qPCR assay.…”
Section: Laboratory Testingmentioning
confidence: 99%